2021
DOI: 10.1186/s40360-021-00485-y
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of calcitriol treatment in non-alcoholic fatty liver patients with different genotypes of vitamin D receptor FokI polymorphism

Abstract: Background Vitamin D deficiency is prevalent in patients with non-alcoholic fatty liver disease (NAFLD), but there are debates on the usefulness of vitamin D treatment. The interindividual variations in response may be due to different genetic backgrounds. The present study evaluated the efficacy of calcitriol treatment in NAFLD patients with regard to the vitamin D receptor (VDR) genotypes of FokI polymorphism. Methods The study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 31 publications
1
23
0
Order By: Relevance
“…A total of 19 records were further excluded at this stage since they did not report the outcome of interest. Finally, a total of 12 studies fulfilled the eligibility criteria [20][21][22][23][24][25][26][27][28][29][30][31].…”
Section: Search Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 19 records were further excluded at this stage since they did not report the outcome of interest. Finally, a total of 12 studies fulfilled the eligibility criteria [20][21][22][23][24][25][26][27][28][29][30][31].…”
Section: Search Resultsmentioning
confidence: 99%
“…A total of 12 studies consisting of at least 18,012 participants combined reported the outcome of interest [20][21][22][23][24][25][26][27][28][29][30][31]. These studies were conducted in 2010 to 2022.…”
Section: Characteristics Of Studies Reporting the Association Between...mentioning
confidence: 99%
See 3 more Smart Citations